The Chemistry of Metal–Organic Frameworks. Synthesis, Characterization, and Applications, 2 Bände. Herausgegeben von Stefan Kaskel. (11th January 2017) - Burrows, Andrew D.
Abstract : Wiley‐VCH, Weinheim 2016. 904 S., geb., 299.00 €.—ISBN 978‐3527338740